Banking structure: opacity and specialization - Moherdaui, Gustavo Gerner (2024)
We considered an economy where banks are coalitions of agents that, on the asset side, fund projects that are heterogeneous in terms of their opacity, and develop relationships with entrepreneurs; and on the liability side, meet the liquidity needs of their members by issuing securities backed by projects. Banks are endogenously formed and there exists a unique core banking structure, exhibiting a negative relationship between the size of the bank and the intensity of its specialization, an equilibrium outcome that conforms with empirical evidence. We explore how changes in aggregate uncertainty and idiosyncratic uncertainty impacts the banking structure.